Inspired by Kabuki: Reflections on a Theatrical Experiment with Wilde’s Salomé - Dallas McCurley (Cahiers Victoriens et Edouardiens)
The article first considers the appropriateness of kabuki-inspired stylizations for performance of Wilde’s spectacularly non-realistic play, while stressing what a Japanese kabuki audience would expect that could not be replicated outside of the context of such a knowing audience. The stage space devised for this production is described as a rejection of the illusionism of 3D perspective, and the use of gestures and overall rhythmic dynamics as a fusion of Wildean and kabuki aesthetics, not entirely either. Finally, attention turns to the important kabuki sub-genre of “raw domestic” plays, where the downright sordid is rendered with an eerie beauty; this closing section dwells on the clashing sign-systems through which the play’s disturbing erotics (familial and other) are projected.